Low Intensity Focused Ultrasound for Non-invasive and Reversible Deep Brain Neuromodulation—A Paradigm Shift in Psychiatric Research - Arulpragasam, Amanda R.; van 't Wout-Frank, Mascha; Barredo, Jennifer; Faucher, Christiana R.; Greenberg, Benjamin D.; Philip, Noah S. (Frontiers in Psychiatry, 2022)
This article describes an emerging non-invasive neuromodulatory technology, called low intensity focused ultrasound (LIFU). This technology is potentially paradigm shifting as it can deliver non-invasive and reversible deep brain neuromodulation though acoustic sonication, at millimeter precision. LIFU’s spatial precision, yet non-invasive nature sets it apart from current technologies, such as transcranial magnetic or electrical stimulation and deep brain stimulation. Additionally, its reversible effects allow for the causal study of deep brain regions implicated in psychiatric illness. Studies to date have demonstrated that LIFU can safely modulate human brain activity at cortical and subcortical levels. Due to its novelty, most researchers and clinicians are not aware of the potential applications and promise of this technique, underscoring the need for foundational papers to introduce the community to LIFU. This mini-review and synthesis of recent advances examines several key papers on LIFU administered to humans, describes the population under study, parameters used, and relevant findings that may guide future research. We conclude with a concise overview of some of the more pressing questions to date, considerations when interpreting new data from an emerging field, and highlight the opportunities and challenges in this exciting new area of study.